Langit dan Bumi Baru: Hasil Pembaruan - Dominikus Selfius Bain; Aprianus Ledrik Moimau (Jurnal Silih Asuh : Teologi dan Misi, 2024)
Every believer has the hope that the future life will be one filled with peace. The eternal life obtained by believers through the new heavens and new earth is only understood through the spiritual realm. Many authors have written about the new heaven and new earth with various perspectives and understandings. Through this article, the author would like to explain what the meaning of the new heavens and new earth is, what the new heavens and new earth look like, and how the way of life of people who come from the new heavens and new earth is the result of renewal. Through this article, the author will reveal what the Bible reveals about the new heavens and the new earth, and how we can respond to what God has revealed about the new heavens and the new earth: the result of renewal.